Russia's "impressionable years": life experience during the exit from communism and Putin-era beliefs. Issue 1 (2nd January 2021) - Pyle, William
ABSTRACT: This article links Russians' individual experiences during the late-Gorbachev and early-Yeltsin years to beliefs they espoused in the Putin era, over a decade later. Drawing on the 2006 wave of the Life in Transition Survey, I show that a range of attitudes – including diminished support for markets and democracy and stronger support for reducing inequality – can be explained by whether an individual suffered labor market hardships in the half decade from 1989 to 1994. Subsequent labor market disruptions, surprisingly, bear no such relationship to beliefs in 2006. Relative to the rest of the former Soviet Union, this pattern is unique. Though an explanation is difficult to pin down, one speculative hypothesis is that for Russians, individual economic hardship, in conjunction with the dissolution of the Soviet Union, may have been particularly disorienting. Life experiences during those years of instability, uncertainty, and diminished status may have left a uniquely enduring impression.